Heavy metals capture from water sludge by kenaf fibre activated carbon in batch adsorption - Saeed, A.A.H. (Polish Society of Ecological Engineering (PTIE), 2020)
The Malaysia's wastewater treatment plant has yet to find an environmentally alternative for the sludge treatment before disposal. In majority of cases, the sludge containing a high amount of heavy metals including Fe, Ti, Mn, Zn, As, Cu, Ni, Zr, and Ga, is disposed to the environment through landfill. The recovery of valuable materials such as manganese from the sludge is an alternative path towards zero dumpings of schedule waste as well as a way of reducing the possible pollutant release to the environment. It can be achieved through adsorption, as it provides a cheap yet flexible, method which is simple and easy to implement. Kenaf derived from Hibiscus cannabis was proven as a good adsorbent material for the heavy metals recovery. This project aims at utilizing Kenaf fiber as activated carbon to recover heavy metals from wastewater sludge in batch adsorption. The adsorbent surface area and pore characteristics and elemental analysis were observed under adsorbent characterization. The effect of contact time, sludge pH and temperature to the removal efficiency was investigated. The adsorption isotherm was also studied. The result showed that the developed kenaf activated carbon is a promising adsorbent which might be used for some heavy metals. From batch adsorption study, it was observed that KFAC is able to remove an average 30 of the heavy metal element from the sludge. It was also found that the best removal is achieved in a neutral pH solution, increasing the contact time will increase the equilibrium uptake, while the increasing temperature will increase the percent removal of heavy metals. It was concluded that the Kenaf based activated carbon can be used for the recovery of heavy metals from the wastewater sludge through batch adsorption. Â© 2020 Polish Society of Ecological Engineering (PTIE).